شیكردنەوە و دابەشبوونی شوێنی خزمتگوزارییە تەندروستییەكان لە قەزای سەید صادق - محمد, شاد حمید; عباس, هوشمند جوهر (Sulaimani Journal for Humanities, 2022)
Health service is the main service in our research area especially in recent years, the district has been enormously changed especially in terms of population, in line with that, it can be seen a great development of construction and prosperity and this certainly has reflection on the services. Thus, the adjustment between division of the services in general and health service in particular, the changes, has been occurred, are considered as a big obstruction which planners have faced. The aim of the research is analysing of division of health services in Said Sadiq district, and showing the level of the skills towards the area and then estimating the current and future needs of people in Said Sadiq district. Research plan: the aim of the research requires dividing the research into three sections: in the first section, an introduction of research area has been highlighted and division of health services in Said Sadiq district, in the second section, we analysed the area of health services in the district. In the third section, the evaluation of occupational health service and the future horizon of health services in the district have been emphasised.